2013
DOI: 10.1136/acupmed-2012-010297
|View full text |Cite
|
Sign up to set email alerts
|

Differential Brain Effects of Laser and Needle Acupuncture at Lr8 Using Functional Mri

Abstract: ObjectiveWhile needle acupuncture is a well-accepted technique, laser acupuncture is being increasingly used in clinical practice. The differential effects of the two techniques are of interest. We examine this in relation to brain effects of activation of LR8, a putative acupuncture point for depression, using functional MRI (fMRI).MethodsSixteen healthy participants were randomised to receive low intensity laser acupuncture to LR8 on one side and needle acupuncture to the contralateral LR8. Stimulation was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
0
30
0
4
Order By: Relevance
“…Some scholars proposed that needling ACU can modulate the brain SMN and the DMN. (28,29,41) The research found that stimulation at Neiting (ST 44) selectively activated the bilateral posterior cingulate cortex, a sub-system of the DMN. (42) In the subsequent research, Wang, et al (43) investigated the neural correlates of individual components of Deqi during acupuncture at the right Taichong (LV 3).…”
Section: Acupuncture Modulates Language-related Brain Networkmentioning
confidence: 99%
“…Some scholars proposed that needling ACU can modulate the brain SMN and the DMN. (28,29,41) The research found that stimulation at Neiting (ST 44) selectively activated the bilateral posterior cingulate cortex, a sub-system of the DMN. (42) In the subsequent research, Wang, et al (43) investigated the neural correlates of individual components of Deqi during acupuncture at the right Taichong (LV 3).…”
Section: Acupuncture Modulates Language-related Brain Networkmentioning
confidence: 99%
“…1,2 Recently, acupuncture has been broadly used in clinical treatment abroad including America. 3 Furthermore, laser acupuncture has been developed to stimulate acupuncture points on the outer skin without infection or pain, 4 and used to improve the treatment of brain function, [5][6][7] dental disease, 8,9 and obesity. 10 The laser stimulation is an alternative method for children with needle phobia.…”
Section: Introductionmentioning
confidence: 99%
“…7 Laser-puncture irradiation uses energy of 20 W/ cm 2 , a value equivalent to the effect of stimulation with acupuncture needles, 8 so that stimulation of acupuncture points by a needle or laser beam would result in an equivalent effect. 8,9 Quah-Smith et al 10 indicated that laser-puncture stimulates nerve fibers A-β and non-nociceptive C, while needle acupuncture stimulates the activity of the nerve fibers A-β, A-δ and C (nociceptive and nonnociceptive) that activates precentral gyrus. 10 Application of laser-puncture for wound healing would be shorter in time compared to conventional acupuncture.…”
mentioning
confidence: 99%
“…8,9 Quah-Smith et al 10 indicated that laser-puncture stimulates nerve fibers A-β and non-nociceptive C, while needle acupuncture stimulates the activity of the nerve fibers A-β, A-δ and C (nociceptive and nonnociceptive) that activates precentral gyrus. 10 Application of laser-puncture for wound healing would be shorter in time compared to conventional acupuncture. [9][10][11] However, clinical studies on the effects of laser-puncture in promoting ulcer repair have never been conducted in Indonesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation